How Does the Built Environment Shape Place Attachment in Chinese Rural Communities? - Liangduo Zhang; Chunyang Zhang; Xin Wang (Buildings)
In the course of rural spatial transformation in China, the vicissitudes of the traditional built environment have given rise to the deconstruction of locality, whereas place attachment emerges as the crux for addressing this issue. Considering that current research on how the built environment influences place attachment remains deficient in constructing a multi-dimensional and composite analytical framework from a rural perspective, this paper constructs a ”community–individual” nested analytical framework and establishes a five-dimensional system of rural built environment elements covering roads, boundaries, regions, nodes, and landmarks. On this basis, this paper takes 15 village cases in Leiling Town, Guangdong Province, China, as the research object, using a hierarchical linear model (HLM) to systematically analyze the impact of rural built environment elements on residents’ place attachment. The study finds that 1. At the individual level, the average score of place attachment is 0.61, with females showing significantly higher levels than males, and age and length of residence being positively correlated with place attachment. 2. At the community level, the built environment explains about 15% of the variance in attachment, with the distance from villages to town centers being negatively correlated and building compactness, environmental tidiness, and cultural landmark density being positively correlated. 3. Node–landmark elements have a significantly stronger impact on place attachment than road-boundary and functional-area elements. 4. The influence mechanism follows the identity cycle of “memory identity—place identity—social identity”.